O-linked mucin-type glycosylation regulates the transcriptional programme downstream of EGFR. (8th August 2020) - Tajadura-Ortega, Virginia; Gambardella, Gennaro; Skinner, Alexandra; Halim, Adnan; Van Coillie, Julie; Schjoldager, Katrine Ter-Borch Gram; Beatson, Richard; Graham, Rosalind; Achkova, Daniela; Taylor-Papadimitriou, Joyce; Ciccarelli, Francesca D; Burchell, Joy M
Abstract: Aberrant mucin-type O-linked glycosylation is a common occurrence in cancer where the upregulation of sialyltransferases is often seen leading to the early termination of O-glycan chains. Mucin-type O-linked glycosylation is not limited to mucins and occurs on many cell surface glycoproteins including EGFR, where the number of sites can be limited. Upon EGF ligation, EGFR induces a signaling cascade and may also translocate to the nucleus where it directly regulates gene transcription, a process modulated by Galectin-3 and MUC1 in some cancers. Here, we show that upon EGF binding, breast cancer cells carrying different O-glycans respond by transcribing different gene expression signatures. MMP10, the principal gene upregulated when cells carrying sialylated core 1 glycans were stimulated with EGF, is also upregulated in ER-positive breast carcinoma reported to express high levels of ST3Gal1 and hence mainly core 1 sialylated O-glycans. In contrast, isogenic cells engineered to carry core 2 glycans upregulate CX3CL1 and FGFBP1 and these genes are upregulated in ER-negative breast carcinomas, also known to express longer core 2 O-glycans. Changes in O-glycosylation did not significantly alter signal transduction downstream of EGFR in core 1 or core 2 O-glycan expressing cells. However, striking changes were observed in the formation of an EGFR/galectin-3/MUC1/β-catenin complex at the cell surface that is present in cells carrying short core 1-based O-glycans but absent in core 2 carrying cells.